(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of this study to determine the low-pressure pneumoperitoneum laparoscopic cholecystectomy.Materials and methods: This research comprised a total of 80 patients who were hospitalised for elective laparoscopic cholecystectomy. patients undergoing open cholecystectomy after conversion. The research did not include patients with acute inflammation or any other choledocholithiasis or gallstone-related complications. Every patient was asked for written informed permission after being told about the research.Results: The most prevalent presenting symptom (85%) was pain in the right upper quadrant. All of the patients had cholelithiasis confirmed by ultrasonography but no symptoms of inflammation. The majority of the patients (80%) had numerous gallbladder stones. The gallbladder was normal in 40 instances (50%), distended in 24 cases (30%), and constricted in 16 cases (20%) intraoperatively, cholesterosis was present in 10 cases (12.5%), and biliary sludge was found in 16 cases (20%). There were no severe intraoperative complications. There was no conversion to normal pressure laparoscopic cholecystectomy or open cholecystectomy. The average surgical time was 35.85±5.85 minutes. The visual analogue scale pain ratings for postoperative shoulder tip pain were 4.5±0.33, 2.4±0.12, and 0.22±0.04, respectively, at 5, 10, and 24 hours. In 91.25% of the patients, oral feeds were begun on the first postoperative day. On the 0th postoperative day, 95% of the patients were ambulating. The average length of stay after surgery was 1.2±0.51 days. On average 6 months of follow-up, no serious problems were notedConclusion: Experienced surgeons may safely use low-pressure pneumoperitoneum to perform laparoscopic cholecystectomy with a lower risk of early postoperative problems, such as shoulder tip discomfort. Only the lengthier learning curve holds it back from being optimal for general usage; in certain circumstances, its reduced intraoperative impact on hemodynamics makes it a worthwhile alternative.